Government Implementation of Block chain (International Journal of Innovative Research in Engineering & Management, 2021)
The primary purpose of this study paper is to explore if the  Blockchain technology may be used inside government  services to build a smart government. This article discussed  the beginnings and the possible applications of Blockchain  across numerous sectors, as the underlying technology of  cryptocurrency called Bitcoin. The democratic governance  system was best suitable for Blockchain adoption. Although it  fails to tackle major infrastructure issues, concerning  healthcare, taxation and other basic services, it was considered  the governmental regime that would best benefit from  innovative technologies like Blockchain to deal with public  service provision due to its aim of creating trust and  transparency with its citizens. This paper concludes that while  Blockchain is hype because of its innovation and promises, it  is smart to approach it cautiously in government organizations  since this technology still has to be proven on a wide scale  and is worth a huge effort and expenditure.
Keywords: Bitcoin; Block chain; Democracy; Governments; Services